Managing medical research data with a Web-Interfacing Repository Manager. - Jakobovits, R. M. (American Medical Informatics Association, 1997)
This paper describes the Web-Interfacing Repository Manager (WIRM), a perl toolkit for managing and deploying multimedia data, which is built entirely from free, platform-independent components. The WIRM consists of an object-relational API layered over a relational database, with built-in support for file management and CGI programming. The basic underlying data structure for all WIRM data is the repository object, a perl associative array whose values are bound to a row of a table in the relational database. Based on our experience implementing a target application (the Brain Mapper Console), we describe five stages through which a system passes as it evolves from a primitive file hierarchy to a full-fledged repository console.